2014
DOI: 10.1186/1471-2407-14-319
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of long noncoding RNA GAS5 indicates a poor prognosis and promotes cell proliferation in gastric cancer

Abstract: BackgroundGastric cancer is the second leading cause of cancer death and remains a major clinical challenge due to poor prognosis and limited treatment options. Long noncoding RNAs (lncRNAs) have emerged recently as major players in tumor biology and may be used for cancer diagnosis, prognosis, and potential therapeutic targets. Although downregulation of lncRNA GAS5 (Growth Arrest-Specific Transcript) in several cancers has been studied, its role in gastric cancer remains unknown. Our studies were designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
243
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(250 citation statements)
references
References 31 publications
6
243
1
Order By: Relevance
“…It is thought that low expression of GAS5 is associated with a higher possibility of lymph node metastasis and distant metastasis in non-small cell lung cancer and gastric cancer, although the differences are not significant (P=0.652 and P=0.056, respectively) (17,19). These findings further suggest that lncRNA GAS5 may function as a tumor suppressor and may represent a potential biomarker and new therapeutic target for some cancers.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It is thought that low expression of GAS5 is associated with a higher possibility of lymph node metastasis and distant metastasis in non-small cell lung cancer and gastric cancer, although the differences are not significant (P=0.652 and P=0.056, respectively) (17,19). These findings further suggest that lncRNA GAS5 may function as a tumor suppressor and may represent a potential biomarker and new therapeutic target for some cancers.…”
Section: Discussionmentioning
confidence: 85%
“…GAS5 was originally isolated from NIH 3T3 cells by Schneider et al with the purpose of identifying potential tumor suppressor genes enriched during growth arrest induced by serum starvation (10). GAS5 transcript levels are significantly reduced in a spectrum of cancers including breast, prostate, glioblastoma, renal clear cell, bladder, hepatocellular, pancreatic, non-small cell lung, colorectal, cervical and multiple myeloma (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Importantly, aberrant GAS5 expression was significantly correlated with metastasis in cervical cancer (21) and hepatocellular carcinoma (15).…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNA expression profiling data showed that there were lncRNAs that were differentially expressed between the PDAC tissues and matched adjacent non-tumor tissues. Previous studies showed that dysregulation of lncRNAs expression such as HOTAIR (32,33), HULC (34)(35)(36) and GAS5 (37,38), is a potential molecular marker for diagnostic and therapeutic purposes in several human cancers. There are still lncRNAs as potential novel candidate molecular markers for clinical diagnosis and therapy of PDAC that need to be further identified.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al stated that GAS5 was markedly downregulated in GC tissues, and its low expression correlated with the poor disease-free survival and overall survival of patients with GC. The ectopic expression of GAS5 repressed GC cell proliferation and induced apoptosis in vitro and in vivo through regulating E2F1 and P21 expression [67]. Franklin etal.…”
Section: Function Of Other Lncrnasmentioning
confidence: 99%